Implementing the classroom password game via telehealth among students with intellectual disabilities. Issue 6 (14th December 2022) - Meyers, Lauren M.; Ripple, Hailey; Bates‐Brantley, Kayla; Bobak, Harry; VanderWoude, Tashina; Gadke, Daniel L.
Abstract: Educational institutions are constantly aiming to better meet the academic needs of individuals with disabilities. As more students with disabilities attend postsecondary education settings researchers need to better understand how to apply both academic and behavioral interventions to better serve this population. Group contingencies are widely popular among educational settings to increase academic engagement and manage classroom behavior. More specifically, the classroom password is an independent group contingency intervention, often utilized in classroom settings to increase academic engagement and decrease disruptive and off‐task behaviors. Utilizing a single case design withdrawal design, researchers sought to evaluate the effectiveness of the classroom password intervention to increase academic engagement and decrease disruptive and off‐task behavior. Due to the COVID‐19 pandemic, researchers utilized the classroom password via telehealth. Overall, the current study's results demonstrate that the intervention was effective at increasing academic engagement and decreasing disruptive and off‐task behavior. Furthermore, the intervention was rated high for social validity among most participants. Future studies should continue to explore the effectiveness, generalizability, and maintenance of these results. Practitioner Points: 1. Classroom password showed increase in academic engagement for college students with intellectual disabilities. 2. Classroom password demonstrated high social validity among college students and instructors. 3. Group contingences can be a useful behavior intervention tool for comprehensive transition programs.